Carbon Monoxide Oxidation on Metal‐Supported Monolayer Oxide Films: Establishing Which Interface is Active. Issue 5 (4th January 2018) - Zhang, Ke; Li, Linfei; Shaikhutdinov, Shamil; Freund, Hans‐Joachim
Abstract: Ultrathin (monolayer) films of transition metal oxides grown on metal substrates have recently received considerable attention as promising catalytic materials, in particular for low‐temperature CO oxidation. The reaction rate on such systems often increases when the film only partially covers the support, and the effect is commonly attributed to the formation of active sites at the metal/oxide boundary. By studying the structure and reactivity of FeO(111) films on Pt(111), it is shown that, independent of the film coverage, CO oxidation takes place at the interface between reduced and oxidized phases in the oxide film formed under reaction conditions. The promotional role of a metal support is to ease formation of the reduced phase by reaction between CO adsorbed on metal and oxygen at the oxide island edge. Abstract : The right phase : By studying the structure and reactivity of FeO(111) films on Pt(111), it is shown that, independent of film coverage, CO oxidation takes place at the interface between reduced and oxidized phases of the oxide film formed under reaction conditions. The promotional role of a metal support is to ease formation of the reduced phase by reaction between CO adsorbed on metal and oxygen at the oxide island edge.